The Contribution of Dopamine to the Implementation of Reward Value During the Control of Action - Lauwereyns, Johan (Central Nervous System Agents in Medicinal Chemistry, 2008)
Recent studies show that the behavioral changes associated with reward expectation may be underpinned by two different cognitive mechanisms: perceptual sensitivity on the one hand, and response bias on the other. Perceptual sensitivity refers to the quality of decision-making as a function of the ratio between signal and noise. The prospect of reward may improve the signal-to-noise ratio for stimuli with a high reward value. In contrast, response bias refers to the a priori likelihood of making one response rather than another, regardless of incoming perceptual information. The prospect of reward may create a response bias by increasing the likelihood of making a response with a high reward value. Thus reward value may be implemented in the control of action through two parallel systems, one system that influences perceptual sensitivity and one system that influences response bias. Electrophysiological recordings suggest that these two systems operate through parallel neural circuits. Evidence for a system that influences perceptual sensitivity is seen in frontal cortex, with neurons that fire differentially following a reliable prediction of reward. Evidence for a system that influences response bias on the basis of reward is seen in the basal ganglia. This system determines the baseline neuronal activity in advance of sensory information processing. Both systems send output to brainstem structures to increase the strength of action representations as a function of incentive. Both systems may be modulated by dopamine input. The cellular action of dopamine, however, depends on the type of receptor involved: Through D2-like receptors dopamine depresses the activity of target neurons, whereas through D1-like receptors dopamine interacts with other receptors. Here I review the evidence in relation to the proposal that the two reward systems - influencing perceptual sensitivity versus response bias - have distinguishable receptor profiles, with reward effects of sensitivity primarily dependent on D1-like receptors, and reward effects of bias mostly due to D2-like receptors.
Keywords: decision making